Analisis Kepuasan Pelanggan Terhadap Kualitas Pelayanan Pada Agrowisata Petik Stroberi (Jurnal Agribisnis Indonesia, 2025)
One form of agrotourism in the agricultural sector that is quite popular is strawberry-picking tourism. To increase the number of visits, tourism managers need to understand the strengths and weaknesses of the services offered in order to formulate appropriate improvement priorities. This study aims to identify consumer characteristics, evaluate attributes in the service quality dimension, and analyze the level of visitor satisfaction with strawberry-picking agrotourism. The study was conducted from August 2023 to January 2024 through a survey of 100 visitors who had or were visiting the tourist attraction. The analysis methods employed include descriptive analysis, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The results of the IPA mapping show that there are six attributes in Quadrant I (top priority for improvement), indicating the potential for service growth that needs to be improved. A total of 15 attributes are in Quadrant II, which means that their performance has been in line with expectations and needs to be maintained. Meanwhile, four attributes are in Quadrant III, indicating that these attributes have a low priority for improvement. A CSI value of 84.84% indicates that visitors are satisfied with the services received. These findings provide strategic input for agrotourism managers in formulating targeted improvement steps to improve service quality and maintain visitor satisfaction sustainably.